국내 시멘트 산업의 온실가스 배출 요인 분석 - 이나영; Nayoung Lee; 조용성; Yongsung Cho (자원·환경경제연구, 2025)
본 연구는 국내 시멘트 산업의 온실가스 배출 특성을 실증적으로 분석하고, 배출 감축을 위한 정책적 시사점을 도출하기 위해 2012년부터 2022년까지 국내 주요 시멘트 제조업체7개사의 데이터를 활용하여 요인분해 분석, 패널 분석, 그리고 동조화 분석을 수행하였다. 요인분해 분석 결과, 매출액 증가와 클링커 생산 효율성의 하락은 온실가스 배출량을 증가시키는 요인으로 작용한 반면, 탄소집약도와 시멘트집약도의 개선, 클링커 의존도의 감소는 온실가스배출량을 감소시키는 긍정적 요인으로 작용하였다. 패널 분석 결과에서는 매출액, 시멘트 대비클링커 비율, 화석연료 소비 및 전력 소비가 온실가스 배출량에 유의미한 영향을 미치는 중요변수로 나타났다. 특히, 매출액 증가가 반드시 배출량 증가로 이어진다고 볼 수 없다는 시사점을 도출하였고, 이 결과는 동조화 분석 결과와 일치한다. 시멘트 산업의 매출액과 CO2 배출량간의 동조화 지수 값은 음수(-)로서 분석 기간 동안 매출액은 증가했지만 온실가스 배출량은 감소하는 탈동조화 현상을 나타냈다. 시멘트 산업은 대표적인 에너지 다소비 산업으로 많은 양의온실가스를 배출하고 있으므로 지속적인 생산 효율성의 개선과 함께 기술 혁신이 필요하다. This study empirically analyzed the characteristics of greenhouse gas emissions in the domestic cement industry. Using data from seven major domestic cement manufacturers from 2012 to 2022, the study performed a decomposition analysis, a panel analysis, and a decoupling analysis to derive policy implications for emission reduction. The decomposition analysis revealed that increases in sales revenue and decreases in clinker production efficiency increased greenhouse gas emissions. Meanwhile, improvements in a carbon intensity and a cement intensity, as well as reductions in clinker dependency, reduced greenhouse gas emissions. Panel analysis results showed that sales, the clinker-to-cement ratio, fossil fuel consumption, and electricity consumption were important variables significantly impacting greenhouse gas emissions. Notably, the results suggested that an increase in sales does not necessarily lead to an increase in CO2 emissions, consistent with the decoupling analysis results. The decoupling index value (DI) between sales and CO2 emissions in the cement industry was negative, indicating a decoupling phenomenon in which sales increased while greenhouse gas emissions decreased during the analysis period. Because the cement industry is a major emitter of greenhouse gases, continuous improvements in production efficiency and technological innovation are necessary.